2011
DOI: 10.1111/j.1476-5381.2010.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits HMGB1 release in LPS‐treated RAW 264.7 cells and increases survival rate of endotoxaemic mice

Abstract: BACKGROUND AND PURPOSE Recently, metformin, a well‐known anti‐diabetic drug, has been shown to possess anti‐inflammatory activities. This study investigated the effect of metformin on the expression of pro‐inflammatory cytokines including high mobility group box 1 (HMGB1) in lipopolysaccharide (LPS)‐treated animals and cells. EXPERIMENTAL APPROACH We investigated whether metformin inhibits the release of HMGB1 in LPS‐treated RAW 264.7 cells and increases survival rate in endotoxaemic mice (lethal endotoxaemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 47 publications
10
98
1
Order By: Relevance
“…Zhao et al, (35) have shown that AICAR-mediated AMPK activation reduced endotoxininduced acute lung injury in mice. Another study showed that administration of AMPK activator metformin (anti-diabetic drug) increased the survival rate of endotoxemic mice (36). Creighton et al (27) have demonstrated that AMPK␣1 signaling promotes the endothelial barrier repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al, (35) have shown that AICAR-mediated AMPK activation reduced endotoxininduced acute lung injury in mice. Another study showed that administration of AMPK activator metformin (anti-diabetic drug) increased the survival rate of endotoxemic mice (36). Creighton et al (27) have demonstrated that AMPK␣1 signaling promotes the endothelial barrier repair process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, release of HMGB1, histones and mitochondrial proteins are known to increase the sever- (68)(69)(70)(71). Of note, AMPK activators, including metformin, were shown to diminish acute inflammatory injury of lung or liver as well as decrease the release of DAMPs and improve mortality in experimental models of LPS-induced sepsis (5,29,36). Although antibiotics are sufficient to kill bacteria, the combination of metformin and antibiotics may have additional benefit in sepsis, particularly as metforminstimulated neutrophils have increased chemotaxis and bacterial uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that besides their ability to regulate cellular metabolism (27), metformin and other AMPK activators can decrease the severity of organ injury in acute inflammatory states (28), including LPS-induced liver injury or acute lung injury (29,30). Metformin, berberine or aminoimidazole carboxamide ribonucleotide (AICAR) were all shown to diminish activation of the tolllike receptor 4 (TLR4)/NF-κB signaling cascade, as well as to release of proinflammatory mediators of neutrophils and macrophages, and also to enhance endothelial integrity in vitro and in models for sepsis (31)(32)(33)(34)(35)(36). In addition, metformin enhances host defense mechanisms by facilitating the chemotaxis and maturation of T cells (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein levels, which are elevated in pilocarpine-induced status epilepticus (Holtman et al, 2013),and may be a biomarker of de-novo depression risk in bipolar disorder (Walker et al, 2014), is lowered by metformin (Oriaifo et al, 2014) which also decreases COX 2 levels (Luchetti et al, 2008) that may be upregulated by NF-kappa B (Crofford et al, 1997) and important for epileptogenesis (Loscher et al, 2010). Metformin and other AMPK activators such as valproate may acutely and chronically suppress TLR 4 signaling (Soraya et al, 2014) and high-mobility group box-I (HMGBI) (Tsoyi et al, 2011) important for genesis of proinflammatory cascades, insulin resistance, bipolar disorder and epileptogenesis showing a convergence of mechanisms amongst these disorders.…”
Section: Type 2 Diabetes Mellitus Drug Addiction Bipolar Disorder Amentioning
confidence: 99%